ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN DI KOPI JAGA CIREBON - Agus, Ivan; Ritonga, Roozana Maria (Jurnal Ilmiah Global Education, 2023)
In 2019 Kopi Jaga Cirebon joined the cafe industry in Indonesia and succeeded in surviving until now for a period of 4 years. Kopi Jaga Cirebon always maintains its existence in the sector of coffee drinks and non-coffee. In preserving its existence, Kopi Jaga Cirebon also creates a comfortable cafe atmosphere equipped with public facilities so that Kopi Jaga Cirebon customers can enjoy drinks while relaxing at Kopi Jaga Cirebon. This research was conducted to find out how influential the store atmosphere towards the customers' purchasing decisions at Kopi Jaga Cirebon. To find out this, the researcher conducted the study using a quantitative method using multiple linear regression analysis along with the result of the Hypothesis Test. The researcher used ways by spreading questionnaires and observation for collecting data. The result of the T-test is T count > T table. Then, the significance value is 0.00 < 0.05. Therefore, the store atmosphere gives some positive effects on the purchasing decisions at Kopi Jaga Cirebon. The formulation of the multiple linear regression test equation is Y = 11.401+0.240X1+0.167X2+0.640X3+0.145X4 wherein every time there is a store atmosphere there will be an increase of 34.6% to the purchasing decision obtained from the test results of the coefficient of determination. The conclusion is that store atmosphere influences purchasing decisions at Kopi Jaga Cirebon so that managers can maintain and improve each indicator of the store atmosphere (X) to improve each indicator on purchasing decisions (Y).